Zimbabwe's Cultural Heritage - Nyathi, Pathisa, 1951- (Book collections on Project MUSE., 2005)
Zimbabwe's Cultural Heritage won first prize in the Zimbabwe Book Publishers Association Awards in 2006 for Non-fiction: Humanities and Social Sciences. It is a collection of pieces of the culture of the Ndebele, Shona, Tonga, Kalanga, Nambiya, Xhosa and Venda. The book gives the reader an insight into the world view of different peoples, through descriptions of their history and life events such as pregnancy, marriage and death. ""...the most enduring book ever on Zimbabwean history. This book will help people change their attitude towards each other in Zimbabwe."" - Zimbabwe Book Publishers.